Efektivitas Metode PQRST untuk Meningkatkan Keterampilan Membaca Pemahaman Teks Eksplanasi - Lutfiatun Muhibbah (Jurnal Didaktika Pendidikan Dasar, 2023)
This study aims to improve reading comprehension skills of explanatory texts using the PQRST (preview, question, read, state, test) method in 5th grade at SD Negeri 3 Gunungsari, West Lombok district. This type of research is an experimental design one group pretest-posttest, which is a research design by conducting the first observation (pretest) which allows researchers to examine changes (cognitive, affective and psychomotor that occur in the second observation (posttest). The sample in this study was taken using saturated sampling is the determination of the sample when all members of the population are used as a sample of 46 students. The data analysis used was descriptive statistics and paired sample t-test. The results of the t test show that the significance value is 0.000 <0.05 so H0 is rejected and H1 is accepted. The results of this study are 1) there is a significant difference between the learning outcomes of pretest and posttest reading comprehension skills using the PQRST method (preview, question, read, state, test). 2) the use of the PQRST method is effective in increasing reading interest and reading comprehension skills of explanation texts in grade 5 SD negeri 3 Gunungsari.